2011
DOI: 10.1186/1758-5996-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and dietary components are associated with coronary artery disease risk score in free-living adults: a cross-sectional study

Abstract: BackgroundCoronary artery disease (CAD) is among the main causes of death in developed countries, and diet and lifestyle can influence CAD incidence.ObjectiveTo evaluate the association of coronary artery disease risk score with dietary, anthropometric and biochemical components in adults clinically selected for a lifestyle modification program.Methods362 adults (96 men, 266 women, 53.9 ± 9.4 years) fulfilled the inclusion criteria by presenting all the required data. The Framingham score was calculated and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…MetS is closely related to increased body fat mass, visceral fat deposition, and insulin resistance, which constitute clinical conditions that require nutritional care. Additionally, MetS pathophysiology includes several comorbities such as inflammation, oxidative stress, pro-thrombotic, and pro-atherogenic processes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…MetS is closely related to increased body fat mass, visceral fat deposition, and insulin resistance, which constitute clinical conditions that require nutritional care. Additionally, MetS pathophysiology includes several comorbities such as inflammation, oxidative stress, pro-thrombotic, and pro-atherogenic processes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence shows that MetS predicts the development of CVD [11][12][13]20]. Takahashi showed that individuals with MetS have a four-fold greater probability of high CAD risk score [3]. Also, the results of other studies indicate greater probability for an increase risk of CVD in people with MetS [21].…”
Section: Discussionmentioning
confidence: 72%
“…Cardiovascular diseases (CVD) are a significant cause of death in Europe and worldwide [1][2][3][4]. In Poland CVD caused 46.0% of all deaths in 2010 [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that hypertensive individuals showed higher plasma glucose, glycemia, total cholesterol, triglycerides and LDL-C levels, which increases the risk of cardiovascular diseases 30 . According to Schaan et al 39 , individuals with some degree of abnormal glucose homeostasis had a higher prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This fact can also be explained by the low fiber consumption in both groups. It is known that individuals with high intake of dietary fiber may have significantly lower risk for developing coronary heart disease, infarction, hypertension, diabetes and obesity 29,30 .…”
Section: Discussionmentioning
confidence: 99%